Analysis of the early clinical outcomes of arthroscopic debridement in the treatment of shoulder tuberculosis - Yanwei He; Juncai Liu; Zhi Wang; Peng Zhou; Xiangtian Deng; Li Yang; Zan Chen; Zhong Li (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background Due to atypical clinical symptoms, it is difficult to diagnose joint tuberculosis infection, which often results in misdiagnosis and missed diagnosis. It is easy to cause joint disability. And there are few reports of using arthroscopy to diagnose and treat shoulder tuberculosis. This case series aims to introduce the clinical outcomes of arthroscopic treatment of shoulder tuberculosis. Methods Twenty-nine patients with shoulder tuberculosis from September 2013 to February 2019 were included (10 males, 19 females; age range from 22 to 69; the average age is 37.6 years). All patients underwent arthroscopic lesion debridement, with preoperative and postoperative regular use of isoniazid, rifampicin, pyrazinamide, and streptomycin quadruple anti-tuberculosis drugs. The erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) were recorded before and at the last follow-up. The shoulder function was evaluated according to the visual analogue scoring method (visual analogue scale, VAS) pain score and Constant score. Results Twenty-nine patients were followed up from 12 months to 2 years, and the average follow-up time was 15.7 months. The pathological diagnosis of all patients after surgery was shoulder tuberculosis. No serious complications were found at the last follow-up, and the incision healed well. VAS pain score, Constant score, ESR, and CRP at the last follow-up were significantly improved compared with those before treatment (P < 0.05). Conclusion On the basis of the standard use of anti-tuberculosis drugs before and after surgery, shoulder arthroscopy is used to treat early and mid-term shoulder tuberculosis, which can be diagnosed by direct observation under the arthroscope and postoperative pathological examination. It has the advantages of thorough lesion removal, minimal invasiveness, rapid recovery, and reliable clinical effect.